Clinical picture of ankylosing spondylitis in HLA-B27 positive and negative patients - Sh. F. Erdes; K. V. Sakharova (Современная ревматология, 2023)
The link between the HLA-B27 gene and ankylosing spondylitis (AS) has been known for almost 50 years. During this time, it has been discovered that some of the clinical manifestations of the disease are uniformly associated with the disease in almost all populations, while the other part depends on the ethnicity of the patients. Unique associations characteristic only of certain ethnic groups are also periodically described.   Objective: to analyze the clinical features of the inpatient population with AS in relation to their HLA-B27 status.   Material and methods. Cross sectional study of 200 consecutive AS patients admitted to the rheumatology department of the V.A. Nasonova Research Institute of Rheumatology. All patients underwent standard clinical examination recommended for assessment of AS activity and functional status. The levels of transaminases, uric acid, urea, creatinine, interleukin (IL) 6 and IL17 in blood serum were also examined.   Results and discussion. HLA-B27 was detected in 166 (83 %) of 200 patients with AS (in 89.8 % of men and in 73.2 % of women; p = 0.003). Among HLA-B27 positive patients with AS, 63.9 % were men, and among HLA-B27 negative patients, 35.3 % were men (p = 0.002). The mean age of AS onset was 5 years higher in HLA-B27-negative patients, and the disease was about 2 times less likely to occur in childhood in them. Syndesmophytes were detected in 25 % of HLA-B27 positive patients and in 15 % of patients who did not have this antigen (p > 0.05). Syndesmophytes were found in 31.1 % of HLA-B27 positive and 25 % of HLA-B27 negative men. 15 % of women with HLA-B27 and 9 % of women without this antigen had syndesmophytes (p = 0.022). Inflammatory bowel disease was more common in HLA-B27-negative patients, whereas uveitis and psoriasis were less common. Activity rates and incidence of arthritis and enthesitis were similar in HLA-B27 positive and negative patients. Serum concentration of IL17 was six times higher in HLA-B27 negative patients than in HLA-B27 positive patients (p = 0.012).   Conclusion. In the Russia’s AS patient population there are associations with HLA-B27, characteristic for most ethnic groups (e. g., earlier onset of the disease) and associations not found in all ethnic groups (e. g., a more severe course, a higher incidence of arthritis and enthesitis). In addition, the concentration of IL17 in the blood serum of HLA-B27 negative patients was six times higher than that of HLA-B27 positive patients. This may indicate non-canonical mechanisms of pathogenesis of AS that develop in the absence of the HLA-B27 gene, which requires further research.